Napoleon's Military Maxims - Napoleon I, Emperor of the French; Edited and annotated by Cairnes, William E. (Mineola, NewYork Dover Publications, Inc., 2004)
This classic brings together a rich sampling of the knowledge and wisdom of one of history's greatest military commanders. The concise text not only provides a fascinating glimpse of the French leader's intellectual ability for conducting military operations but also reveals his thoughts, theories, and commentaries on waging war and the art of conducting statecraft. Equally relevant to today's entrepreneur, the book is packed with maneuvers that can be applied just as easily to increasing revenues on the battlefield of commerce.
Keywords: Military art and science -- Napoleon I, Emperor of the French, 1769-1821